Perlindungan Hukum Terhadap Anak Korban Tindak Pidana Kekerasan Oleh Dinas Pemberdayaan Perempuan, Perlindungan Anak, Pengendalian Penduduk, dan Keluarga Berencana (Dp3ap2kb) Kota Padang - Trisanti, Trisanti; Zurnetti, Aria; Khairani, Khairani (Universitas Ekasakti, 2023)
Children are very vulnerable to becoming victims of crime, many children are targets of acts of violence. In Padang city violence against children in 2021 there was 63 cases of violence recorded. Based on Article 59 paragraph (1) of Law Number 35 of 2014 concerning Child Protection, local governments are obliged to provide protection for child victims. This research focuses on two issues, First: How is the legal protection of child victims of violent crimes committed by DP3AP2KB Padang City, Second: How is the implementation of legal protection for child victims of violent crimes committed by DP3AP2KB Padang City.This study uses empirical juridical research methods with analytical descriptive characteristics. Sources were obtained from interviews, reports and documents. Secondary data comes from related laws and regulations, articles, journals, and internet sites. The results of the research, First, the legal protection carried out by DP3AP2KB is to provide consulting services and legal process assistance to ensure the fulfillment of children's rights so that they can recover and be able to carry out social functions in their environment, social field. Second, the implementation of legal protection for child victims of violent crimes by DP3AP2KB experienced several obstacles, namely a lack of human resources, a lack of special experts such as child clinical psychologists and a lack of budget, facilities and infrastructure. so it must coordinate with other agencies.